A children's champion for Scotland - Susan Elsley (Scottish Journal of Residential Child Care)
Scottish children look likely to get their own Children’s and Young People's Commissioner in the near future. After many years campaigning, organisations working with children and young people now see light at the end of the proverbial tunnel with the recent positive steps towards the establishment of a Commissioner's Office in Scotland. The Education, Culture and Sport Committee of the Scottish Parliament completed their inquiry into a Children's Commissioner earlier this year and published their report (Scottish Parliament, 2002). This endorsed the Committee's support for the establishment of a Commissioner in Scotland. The Scottish Executive, in its response to the report, stated that there was, in principle, a good case for a Commissioner for Children and Young People. The next step will be to introduce a non-executive bill, led by the Education, Culture and Sport Committee into the Scottish Parliament. This is hoped to be in the autumn of 2002 to meet the demands of the legislative timetable in advance of the Scottish Parliamentary elections in 2003.